1975
DOI: 10.1017/s0022172400047276
|View full text |Cite
|
Sign up to set email alerts
|

The differential transmissibility of myxoma virus strains of differing virulence grades by the rabbit flea Spilopsyllus cuniculi (Dale)

Abstract: SUMMARYLaboratory studies showed that few rabbit fleas (SpilopsyllUs cuniculi (Dale)) transmitted myxomatosis after removal from wild rabbits (Oryctolagus cuniculus (L)) that had been infected for fewer than 10-12 days, irrespective of the virulence of the myxoma virus strain involved. Rabbits infected with fully virulent (Grade I) strains died within 10-15 days and few fleas from these hosts became infective; averaging all the samples taken, 12 % of the fleas were infective. Also, few fleas acquired infectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 18 publications
0
44
1
Order By: Relevance
“…However, in an outbreak caused by a fully virulent strain, spread of the disease would be less effective than with a moderately attenuated strain (Mead-Briggs & Vaughan, 1975) and, although individual infected rabbits would die more quickly, the length of the outbreaks would probably be similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in an outbreak caused by a fully virulent strain, spread of the disease would be less effective than with a moderately attenuated strain (Mead-Briggs & Vaughan, 1975) and, although individual infected rabbits would die more quickly, the length of the outbreaks would probably be similar.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the predominance of such strains was due to more effective transmission by mosquitoes in Australia (Fenner, Day & Woodroofe, 1956) and by the rabbit flea in Britain (Mead-Briggs & Vaughan, 1975). Fenner & Ratcliffe (1965) postulated that, in resistant rabbits, strains of higher virulence would be more effectively transmitted and they predicted that the development ofresistance in wild rabbits would lead to an increase in the virulence of field strains of virus.…”
Section: Introductionmentioning
confidence: 99%
“…Myxomatosis is normally transmitted between host rabbits when virus particles adhere to the piercing mouthparts of a biting insect vector. In Britain the rabbit flea, Spilopsyllus cuniculi, is the most important vector of the disease (1) and its role in transmitting different myxoma virus strains has been investigated (2,3); other blood sucking insects may play a minor role as vectors in some circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…In 1970In , 1974In and 1975 small numbers of rabbits were bred in captivity from adult stock captured in the study area. All rabbits were held in captivity for at least 3 months, to ensure that any myxoma virus antibodies acquired from immune does would have decayed.…”
Section: Rabbitsmentioning
confidence: 99%